Commercial aviation safety - Rodrigues, Clarence C. (McGraw-Hill, 2012)
"Presenting current practice and procedures from all major air traffic and regulatory agencies, this book covers the entire commercial aviation safety system--from human safety to accident investigation"-- |c Provided by publisher.